Private insurance, public welfare, and financial markets: Alpine and Maritime countries in comparative-historical perspective - Arjen van der Heide; Sebastian Kohl (Max Planck Institute for the Study of Societies, 2022)
Contemporary capitalist societies use different institutions to manage economic risks. While different public welfare state and financial institutions (banks, capital markets) have been studied across coordinated and liberal market economies, this paper adds the private insurance sector to the study of countries' security arrangements, following up on Michel Albert's classical distinction between Alpine and Maritime insurance cultures. Building on extensive new insurance data collections (1880-2017) and institutional analysis, this paper corroborates the long-run historical existence of two worlds of private insurance. Maritime countries (USA, GBR, CAN) developed much bigger life and non-life insurance earlier, with no state-associated insurance enterprises and riskier investments steered towards financial markets. Alpine insurance (AUT, DEU, CHE), by contrast, was initially smaller, with strong state involvement, a significant reinsurance tradition and relatively heavy investments in mortgages and property, due to economic and financial backwardness. We argue that the larger and more "Maritime" the insurance sector, the more it made welfare states liberal and securities markets large. Insurance is thus a hidden factor for countries' varieties of capitalism and world of welfare. The recent convergence on the Maritime model, however, implies that the riskier and risk-individualizing type of private insurance has added to privatization and securitization trends everywhere. – – Moderne kapitalistische Gesellschaften bedienen sich verschiedener Institutionen, um wirtschaftliche Risiken zu managen. Während wohlfahrtsstaatliche und Finanzinstitutionen (Banken, Kapitalmärkte) in koordinierten und liberalen Marktwirtschaften bereits hinreichend untersucht wurden, wird in diesem Beitrag der private Versicherungssektor in die Untersuchung der Sicherheitsarrangements der Länder einbezogen, aufbauend auf Michel Alberts klassischer Unterscheidung alpiner und maritimer Versicherungskulturen. Mit einer neuen Sammlung von Versicherungsdaten (1880-2017) und einer institutionellen Analyse bestätigt dieses Papier die langfristige historische Existenz zweier Welten privater Versicherung. Die maritimen Länder (USA, GBR, CAN) entwickelten früher viel größere und weniger staatsregulierte Lebens- und Schadensversicherungen mit risikoreicheren Investitionen, die auf die Finanzmärkte gelenkt wurden. Die alpine Versicherung (AUT, DEU, CHE) war dagegen anfangs kleiner, mit einer ausgeprägten staatlichen Beteiligung, einer bedeutenden Rückversicherungstradition und relativ hohen Investitionen in Hypotheken und Immobilien, was auf die wirtschaftliche und finanzielle Rückständigkeit zurückzuführen ist. Wir argumentieren, dass je größer und "maritimer" der Versicherungssektor war, desto mehr hat er die Wohlfahrtsstaaten liberalisiert und die Wertpapiermärkte vergrößert. Das Versicherungswesen ist somit ein versteckter Faktor für die verschiedenen Kapitalismusformen und Wohlfahrtssysteme der Länder. Die jüngste Konvergenz hin zum maritimen Modell bedeutet jedoch, dass die risikoreichere und risikoindividualisierende Art der privaten Versicherung überall zu Privatisierungs- und Verbriefungstendenzen beigetragen hat.
hdl:21.11116/0000-000A-F186-E
Keywords: 300; financial development; historical comparison; insurance; varieties of capitalism; welfare; finanzielle Entwicklung; historischer Vergleich; Spielarten des Kapitalismus; Versicherungen; Wohlfahrtsstaat